Mental Health Problems of U.S. Students Studying Abroad - Poyrazli, Senel; Mitchell, Michael A. (Journal of International Students, 2020)
This study describes mental health problems and needs among a sample of college students from the United States studying abroad in Italy. Overall, students surveyed had relatively low clinical diagnostic thresholds for psychological distress. Individual symptoms were more prevalent and included difficulty sleeping, eating problems (poor appetite or overeating), irritability, and anxiety. Findings from this study offer recommendations for study abroad professionals to screen, monitor, and engage students about their mental health well-being while abroad.